2021
DOI: 10.3390/antiox10101627
|View full text |Cite
|
Sign up to set email alerts
|

Omega−3 Polyunsaturated Fatty Acids (PUFAs): Emerging Plant and Microbial Sources, Oxidative Stability, Bioavailability, and Health Benefits—A Review

Abstract: The omega−3 (n−3) polyunsaturated fatty acids (PUFAs) eicosapentaenoic acid (EPA) and docosahexaenoic (DHA) acid are well known to protect against numerous metabolic disorders. In view of the alarming increase in the incidence of chronic diseases, consumer interest and demand are rapidly increasing for natural dietary sources of n−3 PUFAs. Among the plant sources, seed oils from chia (Salvia hispanica), flax (Linum usitatissimum), and garden cress (Lepidium sativum) are now widely considered to increase α-lino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
116
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(118 citation statements)
references
References 151 publications
(220 reference statements)
1
116
0
1
Order By: Relevance
“…The non-heme iron content has capacity to catalyze lipid oxidation [ 34 , 35 ], thus justifying the decrease in heme iron content and increase values and increase in TBARS values, which is an indicator of secondary oxidation products such as malondialdehyde (MDA), which are formed during the reaction of lipid oxidation reaction [ 36 , 37 ]. The application of the onion edible film had no effect on the lipid peroxidation process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-heme iron content has capacity to catalyze lipid oxidation [ 34 , 35 ], thus justifying the decrease in heme iron content and increase values and increase in TBARS values, which is an indicator of secondary oxidation products such as malondialdehyde (MDA), which are formed during the reaction of lipid oxidation reaction [ 36 , 37 ]. The application of the onion edible film had no effect on the lipid peroxidation process.…”
Section: Discussionmentioning
confidence: 99%
“…The application of the edible onion film in beef burger patties provided, throughout the storage period, less microbial growth and proliferation, demonstrated the antimicrobial potential of onion [ 40 ]. The high antimicrobial activity of onion peel residue extracts was observed against Escherichia coli , Pseudomonas fluorescens , Bacillus cereus , and Aspergillus niger fungi, Trichoderma viride and Penicillium cyclopium [ 37 ]. Behbahani and Imani [ 31 ] observed that edible coatings containing vegetable extracts have the potential to improve the microbial safety and shelf life of beef and this can occur by several mechanisms, including attacking the phospholipid bilayer of the cell membrane, interrupting enzymatic systems and damaging the genetic material of bacteria that, when they come into contact with the food surface, release the active compounds and, as a result, end up helping to inhibit/delay bacterial multiplication [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, PUFAs are easily oxidized, leading to off-flavors, a decrease of the nutritional value, and even formation of potentially toxic compounds [280]. Moreover, PUFAs are susceptible to chemical modifications, such as metal-catalyzed autoxidation and hydrogenation, because of their multiple carbon-carbon double bonds vulnerable to electrophilic attack [24]. Chen and co-authors [281] showed that storage of microalgal biomass leads to lipid hydrolysis, in particular when stored as a wet paste at temperatures above the freezing point, but sometimes also as spray-and freeze-dried microalgal biomass [272].…”
Section: Extraction Purification and Stability Of Pufasmentioning
confidence: 99%
“…It is common knowledge that PUFA consumption is related to various health benefits for humans, as well as the improvement of metabolic rates, the regulation of blood pressure and glucose level, and the protection against numerous diseases, including some types of cancer [22]. Clinical and epidemiological studies have shown that an eicosapentaenoic acid (EPA-C 20:5 ω3)-rich diet contributes to minimizing risks of cardiovascular diseases [23,24]. Docosahexaenoic acid (DHA-C 22:6 ω3) and arachidonic acid (AA-C 20:4 ω6) are important to avoid impairments in infant brain development and cognitive deficiency [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, GPLs, commonly known as phospholipids (PLs), TAGs, and sterols (mainly cholesterol in animals), are the most common type of fat found in plants and animals [3]. Moreover, in microalgae, thraustochytrids, fish, krill, and plant seeds, the nutritionally important omega-3 polyunsaturated fatty acids (PUFAs) are generally attached to TAGs [4,5].…”
Section: Introductionmentioning
confidence: 99%